2020
DOI: 10.1088/2053-1591/ab8fec
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZSM-5 zeolite from fly ash and its adsorption of phenol, quinoline and indole in aqueous solution

Abstract: This work tries to synthesize ZSM-5 zeolite using fly ash (FA) by hydrothermal method and study the adsorption effect of the zeolite on phenol, quinoline and indole in aqueous solution. The zeolites were characterized with x-ray diffraction (XRD), scanning electron microscopy (SEM), x-ray fluorescence (XRF), fourier transformation infrared (FTIR) and N 2 adsorption-desorption isotherm. The characterization results showed that HZSM-5 zeolite was successfully synthesized. The higher mass ratio of sodium carbonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Fly ash is one of the principal wastes produced by coal burning in power plants. Because the major components of fly ash are silica and alumina that are chemically comparable to the components of zeolite, several studies have focused on converting fly ash to ZSM‐5 zeolite 80‐82 . Rice husk ash is an agricultural by‐product with a high content of amorphous SiO 2 that can be collected when the husks are treated with alkali solutions 84,87 .…”
Section: Natural Sourcesmentioning
confidence: 99%
See 3 more Smart Citations
“…Fly ash is one of the principal wastes produced by coal burning in power plants. Because the major components of fly ash are silica and alumina that are chemically comparable to the components of zeolite, several studies have focused on converting fly ash to ZSM‐5 zeolite 80‐82 . Rice husk ash is an agricultural by‐product with a high content of amorphous SiO 2 that can be collected when the husks are treated with alkali solutions 84,87 .…”
Section: Natural Sourcesmentioning
confidence: 99%
“…From 2018 to present, scientists have paid close attention to the synthesis and application of ZSM‐5 from fly ash, as evidenced by the growing number of publications. Some research has focused on the optimization of crystal formation 81 or the external surface phenomena in the dealumination and desilication of ZSM‐5, 142 while others concentrated on the catalytic 83,125,143,144 or adsorptive performance 80,90,126,145,146 . To be more specific, ZSM‐5 has been successfully used to eliminate volatile organic compounds (VOCs) or hazardous substances in aqueous solutions via adsorption.…”
Section: Natural Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the metal addition to the support (solid acid) often affects the catalyst's crystallinity, specific surface area, and morphology. Meanwhile, several studies showed an excellent catalyst gives a good performance related to the high crystallinity [3], high surface area [4], porous morphology [5,6], and metal distribution on support [5,7]. Therefore, it is crucial to study the effects of metal addition to support the bifunctional catalyst of direct DME synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%